Stereochemical dependence of NMR geminal spin-spin coupling constants - Contreras, Ruben Horacio (2008)
In this work it was sought to explore the versatility of germinal spin–spin coupling constants, ²JxySSCCs, as probes for stereochemical studies. A set of compounds, where their experimental ²JxySSCCs through the X–C–Y molecular fragment are predicted to be sensitive to hyperconjugative interactions involving either bonding or antibonding orbitals containing the C carbon atom (‘coupling pathway’), were analyzed. SSCC calculations were performed for some selected examples using the second order polarization propagator approximation (SOPPA) method or within the DFT-B3LYP framework. Hyperconjugative interactions were calculated within the Natural Bond Orbital (NBO) approach. Results are condensed in two qualitative rules: Rule Iм—hyperconjugative interactions transferring charge into the coupling pathway yield a positive increase to the Fermi contact (FC), contribution to ²Kxy reduced spin–spin coupling constants (RSSCC), and Rule IIм—hyperconjugative interactions transferring charge from the coupling pathway yield a negative increase to the FC contribution to ²Kxy RSSCC.